Development of the Russian Far East and the Arctic: demographic aspect - S. G. Serikov; T. N. Ganina (Вестник университета, 2021)
The article considers the geostrategic territories of the Russian Far East and the Arctic. The paper emphasizes the need to ensure the accelerated socio-economic development of these territories in order to preserve and strengthen the positions of Russia as an energy and mineral-raw superpower. In the course of analyzing the demographic situation, the authors identified the main reasons for the migration movement of the population, and also assessed the impact of the demographic situation on the socio-economic development of the Russian Far East and the Arctic. The study established that the attraction of labor resources to the extractive industry would quickly increase the gross regional product from the use of the existing resource and energy base of the macro region. The use of the natural resource potential of the Far East and the Arctic will strengthen the status of Russia in the international arena as an energy and mineral-raw superpower.